2020
DOI: 10.1002/jbmr.4711
|View full text |Cite
|
Sign up to set email alerts
|

Functional Testing of Bone Morphogenetic Protein (BMP) Pathway Variants Identified on Whole-Exome Sequencing in a Patient with Delayed-Onset Fibrodysplasia Ossificans Progressiva (FOP) Using ACVR1R206H-Specific Human Cellular and Zebrafish Models

Abstract: Bone morphogenetic protein (BMP) signaling is critical in skeletal development. Overactivation can trigger heterotopic ossification (HO) as in fibrodysplasia ossificans progressiva (FOP), a rare, progressive disease of massive HO formation. A small subset of FOP patients harboring the causative ACVR1 R206H mutation show strikingly mild or delayed-onset HO, suggesting that genetic variants in the BMP pathway could act as disease modifiers. Whole-exome sequencing of one such patient identified BMPR1A R443C and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Here, we used the zebrafish embryo as an in vivo model to define the functional domains and type II receptor signaling partners of FOP-associated human Hs-ACVR1 R206H and orthologous zebrafish Dr-Acvr1l R203H , taking advantage of the well-established embryonic dorsalization (C1-C5) and ventralization (V1-V5) phenotypes as a read-out for global BMP signaling. 30,37,[52][53][54] Using HS inducible transgenic lines, mRNA injections, anti-sense morpholino oligomer (MO) injections, and CRISPR/Cas9 Homology Directed Repair (HDR) approaches, we showed that Hs-ACVR1 R206H and Dr-acvr1l R203H exhibit functional differences in embryonic zebrafish. While Dr-acvr1l R203H exhibits WT Dr-acvr1l functions in early embryonic zebrafish; in contrast, Hs-ACVR1 R206H induced ventralized embryonic phenotypes consistent with upregulated BMP signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used the zebrafish embryo as an in vivo model to define the functional domains and type II receptor signaling partners of FOP-associated human Hs-ACVR1 R206H and orthologous zebrafish Dr-Acvr1l R203H , taking advantage of the well-established embryonic dorsalization (C1-C5) and ventralization (V1-V5) phenotypes as a read-out for global BMP signaling. 30,37,[52][53][54] Using HS inducible transgenic lines, mRNA injections, anti-sense morpholino oligomer (MO) injections, and CRISPR/Cas9 Homology Directed Repair (HDR) approaches, we showed that Hs-ACVR1 R206H and Dr-acvr1l R203H exhibit functional differences in embryonic zebrafish. While Dr-acvr1l R203H exhibits WT Dr-acvr1l functions in early embryonic zebrafish; in contrast, Hs-ACVR1 R206H induced ventralized embryonic phenotypes consistent with upregulated BMP signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Wentworth and colleagues 17 and Yamamoto and colleagues 18 provide new insight on FOP pathophysiology pointing to possible future new therapeutic targets.…”
mentioning
confidence: 99%